Redesain Map Rekam Medis Berdasarkan Aspek Anatomi, Fisik, dan Isi di Klinik Fisioterapi - Resta Dwi Yuliani; Suci Ariani; Herista Novia Widanti; Galuh Ratmana Hanum (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2025)
Efforts to realize the implementation of good medical records require supporting elements in the form of medical record folders with a design that meets standards. Medical record folders protect patient documents and simplify the process of identifying, storing, and managing health data. Based on the results of observations at the UMSIDA Physiotherapy Clinic, the medical record folder used is still simple, only made of ordinary paper without a logo, name, clinic address, or columns for writing patient identity and medical record number. This condition has the potential to cause obstacles in the administration and security of patient data. The purpose of this research is to redesign (redesign) medical record folders based on anatomical, physical, and content aspects to make them more professional and functional. The methods used include needs analysis through interviews with users, evaluation of old designs, and the creation of new designs. The redesign was carried out by adding heading elements in the form of the name and address of the clinic, introduction in the form title or medical record folder, and instructions in the form of the text "Confidential Documents." On the body, the patient's identity is contained such as full name and medical record number. From the physical aspect, the folder is designed in the form of a portrait with a size of 21.5 cm × 33.0 cm, using white 260 grams of ivory paper with a blue background. Meanwhile, the content aspects include the identity of the health service facility, the writing "Confidential Document," the patient's name, medical record number, and year of visit. The results of the study concluded that the redesign of the medical record folder has met the anatomical, physical, and content standards needed to support more organized health services.